Aktivitas Antioksidan Ekstrak Etanol Biji Salak Pondoh (Salacca zalacca) Kultivar Nglumut dengan Metode 1,1-Difenil-2-Pikrilhidrazil (DPPH) - Dina Febrina; Rani Prabandari (Universitas Harapan Bangsa, 2021)
Oxidative stress caused by excess production of free radicals in the body can cause degenerative diseases such as hypertension, cardiovascular disease, stroke, diabetes mellitus, cancer and signs of aging. This degenerative disease is caused because the antioxidants in the body are unable to neutralize the increased concentration of free radicals. Utilization of natural ingredients as antioxidants is needed, this is because the use of traditional medicine is considered to have relatively smaller side effects compared to drugs derived from chemicals. Antioxidant testing was carried out using the DPPH method on samples in the form of ethanol extract of the seeds of the salak nglumut cultivar and against ascorbic acid as a comparison. The results showed that the ethanol extract of the seeds of the nglumut cultivars of salak seeds contained secondary metabolites such as alkaloids, polyphenols, tannins, flavonoids and steroids. The ethanol extract of the nglumut cultivars of salak seeds has antioxidant activity in the moderate category with an IC50 value of 115,19 ppm.